The Analysis Of Liquidity Ratio For Civil Service Cooperative Ao' Gading PGRI Ranting Balusu North Toraja Regency - Westerini Lusdani; Rati Pundissing; Chrismesi Pagiu (Proceeding of The International Conference on Economics and Business, 2022)
This research aims to examine the liquidity ratio at the Ao' Gading Civil Servant Cooperative PGRI Ranting Balusu in the North Toraja Regency. This research's data analysis technique is the analysis of the liquidity ratio, which consists of the current ratio and the cash ratio .In 2018, the current ratio was calculated to be 3.51 %; in 2019, it was calculated to be 3.41 %; and in 2020, it was calculated to be 3.31 %. In 2018, the cash ratio was calculated to be 0.71 %, while in 2019 and 2020, it was calculated to be 1.04 % and 1.20 %, respectively. According to the rules set forth by the State Minister for Cooperatives and SMEs of the Republic of Indonesia, the Ao' Gading PGRI Ranting Balusu, North Toraja Regency, current ratio calculation findings indicate that it is not good, According to the decree of the State Minister for Cooperatives and UKM of the Republic of Indonesia, Number 06/M/KUKM/2006, dated May 1, 2006, and the outcomes of the cash ratio calculation at Ao' Gading PGRI Ranting Balusu, North Toraja Regency, they are classified as not good. According to the assessment requirements of the Indonesian Ministry of Cooperatives and UKM, the liquidity of the Ao' Gading PGRI Ranting Balusu Civil Servant Cooperative is rated as poor based on the study conducted with several liquidity ratio formulas, Number 06/M/KUKM/2006 does not mean that it is illiquid but the cooperative does not optimize its current assets because its cash is still too small compared to its receivables even though its current assets are greater than its current liabilities.